Dose Optimization of Ovatide Hormone for Induced Breeding of Freshwater Gang Magur, Hemibagrus Menoda (Hamilton, 1822) (Research in Agriculture Livestock and Fisheries, 2021)
An experiment on induced breeding of gang magur, Hemibagrus menoda (Hamilton, 1822) using Ovatide hormone was carried out at in the Field Laboratory Complex of Faculty of Fisheries, Bangladesh Agricultural University, Mymensingh. This study consists of three treatments each with three replications. The objective of the experiment was to find out the effective dose of Ovatide hormone for induced breeding. A total number of 54 brood fish were used for the experiment among which 36 were male and 18 were female. Brood fish were kept in the ratio of 2♂:1♀ for breeding purpose. Female brood fish were injected at the rate of 7, 5, 3 ml Ovatide/kg body weight while the males were injected with 3, 2.5 and 1.5 ml Ovatide/kg body weight respectively in T1, T2, and T3 at the same time. The brood fish were injected with single dose of Ovatide in all treatments. Ovulation rates were 0%, 100%, 63%; fertilization rates were 0%, 97%, and 90%, and hatching rates were 0%, 95% and 76% in treatments T1, T2, and T3 respectively. Fertilized eggs were incubated for 21-22 h in all the treatments. Higher ovulation rate (100 %), fertilization rate (97%), hatching rate (95%) and survival rate (85%) were found in treatment T2. Therefore, the optimum dose of Ovatide hormone for induced breeding of H. menoda is 2.5 and 5 ml Ovatide/kg body weight of male and female brood fish, respectively.Res. Agric., Livest. Fish.8(1): 171-179, April 2021